Environmental Assessment of Cadmium in Paddy Soils and Rice Grains Adjacent to Limboto Lake: Bioaccumulation and Non-Carcinogenic Health Risks - Tri Septian Maksum; Agung Nurwahid Mancu (Media Publikasi Cendekia Indonesia, 2026)
Cadmium (Cd) in agroecosystems poses risks to environmental quality, food safety, and public health because of its persistence and toxicity. This study assessed Cd concentrations in paddy soils and rice grains around Limboto Lake, Indonesia, evaluated soil contamination status, determined Cd transfer from soil to rice, and estimated potential health risks associated with rice consumption. A descriptive quantitative study was conducted at three rice-growing sites adjacent to the lake. Composite soil and rice grain samples were analyzed using Atomic Absorption Spectrophotometry (AAS). Soil contamination was evaluated using the Contamination Factor (Cf) and Geoaccumulation Index (Igeo), Cd transfer using the Bioaccumulation Factor (BAF), and health risks using the Estimated Daily Intake (EDI) and Target Hazard Quotient (THQ). Soil pH ranged from 3.5 to 5.0, indicating acidic to very acidic conditions that may enhance Cd mobility and bioavailability. Cd concentrations ranged from 0.23–0.29 mg/kg in soils and 0.0019–0.0024 mg/kg in rice grains, both below environmental and food safety standards. Cf indicated moderate contamination, whereas Igeo classified the soils as unpolluted to moderately polluted, reflecting differences in the sensitivity and calculation approaches of the two indices. BAF values <1 indicated that although pH increases mobility, the current concentrations do not lead to significant bioaccumulation. EDI and THQ were below the safety threshold, indicating no significant non-carcinogenic health risk from current rice consumption. Although rice remains safe for consumption, persistent Cd occurrence in soils and rice suggests a potential long-term environmental concern if accumulation continues. Therefore, regular monitoring and soil management, including liming to increase soil pH, are recommended to reduce Cd mobility and maintain food safety in the Limboto Lake agroecosystem.